Impact of long-term sludge application on yield, nutrient uptake and profitability of maize (Zea mays) - VERMA, ANIL KUMAR; MEENA, MAHESH C; DATTA, S P; DWIVEDI, B S; GOLUI, D; KUMAR, ASHOK; LOUHAR, GANPAT; MEENA, RAJKUMAR (The Indian Journal of Agricultural Sciences, 2021)
A field experiment was conducted to evaluate the long-term sewage sludge (SS) and fertilizer impact on yield and farm profitability in maize (Zea mays L.) grown at the ICAR-IARI, New Delhi during 2014-17. The experiment was laid out in a randomized complete block design with eight different treatment combinations comprising of different levels of sludge and fertilizer as follows: T1= control (no sludge and NPK fertilizer), T2= 100% recommended dose of NPK (NPK), T3= 25% N substituted by sludge +75% N + PK, T4= 50% N substituted by sludge + 50% N + PK, T5= 100% N substituted by sludge + PK, T6= Two times of sludge as applied in T5 + PK, T7= Three times of sludge as applied in T5 + PK and T8= NPK+2.5 t sludge/ha. Results revealed that the combined application of sludge @ 2.5 t/ha along with NPK (T8) showed highest grain yield of maize i.e. 5.93 t/ha. Total P, K and micronutrients uptake by straw and grain of maize were found to be highest in T7 treated plot. The maximum gross return, net return and B:C ratio were recorded under NPK along with 2.5 SS t/ha. Application of sludge not only enhanced the crop productivity of maize by supplying major and micronutrients, but also enriched maize grain with micronutrients like Zn and Fe throughout the treatments. Finally, it can be concluded that the treatment T8 i.e. NPK+2.5 SS t/ha could be an effective option for getting higher profitability and better quality yield of maize.